Power to the people - Brockelbank, Ted.; Woollard, William (New York Filmmakers Library)
A discussion of energy alternative systems and the social, economic and environmental considerations of each alternative.
Narrator, William Woollard; editor, Dick Pull.
Keywords: Electric power -- India; Biogas -- India; Power resources -- Zimbabwe; Power resources -- India; Reforestation -- Zimbabwe; Environmental science